Mining for humanity in the deep sea and outer space: The role of small states and international law in the extraterritorial expansion of extraction. (7th February 2019) - Feichtner, Isabel
Abstract: This article explores how Luxembourg and Nauru put their sovereignty to use in order to become global players in what can be considered extraterritorial landgrabs – the turning of the deep seabed and outer space into realms of commercial exploitation. It shows how the international legal framework puts states, however small, into a position to facilitate private enterprises' endeavours to obtain extraterritorial exploitation rights. The article further enquires into the public interest justifications put forward by governments to legitimate their support for the expansion of private resource extraction into the deep sea and outer space. It finds that these justifications are very tenuous; that governments refer to vague notions of economic growth and benefits that may accrue from extraction to an undefined humanity while it remains unclear whether their own populations will obtain any concrete gains. Both case studies illustrate how states, on the basis of international law, facilitate the expansion of private value extraction, thus perverting the redistributive ambitions that may once have motivated the negotiations of the United Nations Convention on the Law of the Sea and the Outer Space Treaty.